“Análisis del fenómeno de ferroresonancia en transformadores de potencia” - Mora Reinozo, Franklin Vinicio (2021)
ABSTRACT Energy transformation is one of the most critical aspects of an electrical power system. The transformer performs an essential function, so the transformer must be protected from events that may affect its integrity. The Ferroresonance causes disturbances within the electrical system, causing voltage variations causing quality and safety problems. This work analyzes the phenomenon of Ferroresonance in Power Transformers. It uses analytical and synthetic research, with literary research, collecting information from different authors and allowing to know in-depth the theoretical principles, causes, and effects characteristic of the phenomenon of ferroresonance. Three simulation tools analyze transient phenomena widely used in the electrical area, such as ATPDraw, PSCAD, and Simulink. These tools aimed to check transformers' response to the ferroresonance phenomenon, determining that switching the phases that feed the transformer is a necessary condition for ferroresonance formation. This influence of the capacitance value and the connection of the transformer's primary winding is also determined. The value of capacitance is decisive in the magnitude of the resulting overvoltage.